2021
DOI: 10.1097/eja.0000000000001636
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone for the treatment of established postoperative nausea and vomiting

Abstract: BACKGROUND Dexamethasone is widely used for the prevention of postoperative nausea and vomiting (PONV) but little is known about its efficacy for the treatment of established PONV.OBJECTIVE To test the antiemetic efficacy of intravenous dexamethasone for the treatment of established PONV in adults undergoing surgery under general anaesthesia and to determine whether there is dose-responsiveness.DESIGN The DexPonv trial is a multicentre, placebo-controlled, randomised, double-blind, dose-finding study. Inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Dexamethasone is used in anaesthesia mainly as an antiemetic agent, 11,12 however, strong evidence is available suggesting that it also is a promising adjunctive analgesic in various surgical interventions 6,7,13,14 . A recent meta-analysis and trial sequential analysis re-confirmed the analgesic potential of dexamethasone in the setting of caesarean delivery 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dexamethasone is used in anaesthesia mainly as an antiemetic agent, 11,12 however, strong evidence is available suggesting that it also is a promising adjunctive analgesic in various surgical interventions 6,7,13,14 . A recent meta-analysis and trial sequential analysis re-confirmed the analgesic potential of dexamethasone in the setting of caesarean delivery 15 .…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Additionally, it has been widely accepted that good analgesia is multimodal, meaning that it will incorporate more than one modality of pain treatment that will act synergistically, target surgical mechanism, reduce opioid requirements and hence improve pain relief and stimulate early recovery. 10 Dexamethasone is used in anaesthesia mainly as an antiemetic agent, 11,12 however, strong evidence is available suggesting that it also is a promising adjunctive analgesic in various surgical interventions. 6,7,13,14 A recent meta-analysis and trial sequential analysis re-confirmed the analgesic potential of dexamethasone in the setting of caesarean delivery.…”
mentioning
confidence: 99%